Peacemaking through Blood in Colossians: An Analysis of the Imagery in Its Graeco-Roman and Jewish Context - Carlos Araújo, Diego dy (Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe, 2023)
In dieser Arbeit wendet Diego dy Carlos Araújo die Erkenntnisse der Frame-Semantik und der konzeptuellen Metapher an, um die verschiedenen Bilder zu untersuchen, die der Ausdruck »Frieden stiften durch Blut« möglicherweise in den Köpfen der implizierten Leser hervorruft.InhaltsübersichtChapter 1: Pax Romana as a Viable Graeco-Roman Frame A. Introduction: Parta victoriis paxB. Pax Romana: A Brief OverviewC. Pax Romana in Asia Minor: The Availability of the FrameD. Conclusion: Peace by Blood Chapter 2: Pax Romana and Peacemaking Through Blood in Colossians A. Introduction: Pax Romana and the Peace of ChristB. Identifying the FramesC. God's Triumph in Christ: Colossians 2.15D. Christ's Peace and God's Triumph on the Cross – Colossians 1.20b and 2.15 in ContextE. The Transforming Power of the MetaphorF. Conclusion: The Triumph of Christ's Peace Chapter 3: Rîb-Controversy as a Viable Jewish Frame A. Introduction: Reconciliation in the Jewish Conceptual WorldB. Rîb-controversy in the Old TestamentC. The »Rîb-Pattern« as a Conceptual FrameD. Conclusion: The Re-establishment of Peace Chapter 4: Courtroom Controversy in Isaiah and Maccabees A. Introduction: God's Servant's »Blood«B. Deutero-Isaiah: Considerations on Method and DelimitationsC. Israel's Deliverance as Second Exodus in Deutero-IsaiahD. Courtroom Controversy in the Book of IsaiahE. Blood and Peace in The Maccabean MartyrologyF. Conclusion: Peace by the »Blood« of God's Servant Chapter 5: Peacemaking Through Blood in Colossians 1.20b: Christ's Cosmic Peace A. Introduction: Superior Blood, Superior PeaceB. The Thematic Structure of Colossians 1.12–23: A Brief AppraisalC. Second Exodus Frame in Colossians 1.12–14D. Deutero-Isaiah Frames in ColossiansE. The Maccabean Martyrology Frame in ColossiansF. The Transforming Power of the MetaphorG. Conclusion: Peace at Last